Pengaruh Blue Light Filter Pada Smartphone Terhadap Tingkat Kelelahan Mata Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Savista, Taya Elsa; Adilah, Rifkah (Universitas Muhammadiyah Sumatera Utara, 2024)
Abstract: The use of smartphones in the digital era like today is increasingly intense in daily life. Not only teenagers and adults, smartphones are also widely used by children, toddlers, and even babies. Blue light filters on smartphones are believed to reduce visual disturbances that occur due to long-term smartphone use. The purpose of this study is to analyze the effect of a blue light filter on the level of eye fatigue of students of the Faculty of Medicine, University of Muhammadiyah North Sumatra (FK UMSU). This research is quasi-experimental with a pre-posttest design. A total of 154 FK UMSU students were divided into 2 groups, the Blue Light Filter Group (BLF) and the Non-Blue Light Filter Group (Non-BLF) with the same number (n1 = n2 = 77). Each group filled out a VFS (Visual Fatigue Scale) questionnaire before and after working on the visual task. The data were analyzed using the Mann-Whitney and Wilcoxon tests. The results showed that the post-test score of the level of eye fatigue in the Non-BLF group was significantly higher than that of the BLF group (P 0.001). There was a significant difference between the pre-test and post-test results of the Non-BLF Group (P 0.001), while the pre-test and post-test results of the BLF Group showed a difference but not significant (P = 0.860). This study shows that the use of blue light filters affects the level of eye fatigue.